Effect of Classical Music Therapy on Blood Pressure Reduction in Hypertension Patients at Hospital - Manurung, Sarida Surya; Herlina, Meriani; Silalahi, Bernita; Noradina, Noradina; Pertiwi, Adinda Kusuma (Universitas Aisyah Pringsewu, 2020)
Hypertension is a common disease in patients due to a decrease in the physiological system, especially in the cardiovascular system. At the moment there is one non-pharmacological method that can lower blood pressure by listening to classical music. The purpose of this research is to find out the influence of classical music. The purpose of this study is to determine the effect of classical music therapy on blood pressure reduction in patients with hypertense. This research is an experimental research with cross sectional design conducted in December-February 2019 at Imelda General Hospital Medan, East Medan District. The sample in this study was hypertension patients as many as 31 people collected by concesutive sampling. Heipertensi obtained by blood pressure examination and interview history of consumption of antihypertensive drugs. The results of the study obtained a sample of 31 people, namely 15 men and 16 women, and then the sample was given classical music therapy. With the result that as many as 16 samples experienced a decrease in blood pressure and 15 samples did not experience a decrease in blood pressure. Based on the results of the analysis of T-test and Chi-Square obtained the influence of classical music on the decrease in blood pressure of patients with hypertension (p value= 0.000). Then the decrease in blood pressure in patients with hypertension.Abstrak: Hipertensi adalah penyakityang sering terjadi pada pasien dikarenakan terjadi penurunan dari sistem fisiologis terutama pada sistem kardiovaskular. Pada saat ini ada satu metode non-farmakologi yang dapat menurunkan tekanan darah yaitu dengan mendengarkan musik klasik. Tujuan penelitian ini adalah untuk mengetahui pengaruh musik klasik. Tujuan penelitian ini adalah untuk mengetahui pengaruh terapi musik klasik terhadap penurunan tekanan darah pada pasien penderita hipertensa. Penelitian ini merupakan penelitian experimental dengan rancangan cross sectional yang dilaksanakan pada bulan Desember-Februari 2019 di Rumah Sakit Umum Imelda Medan, Kecamatan Medan Timur. Sampel pada penelitian ini adalah pasien Hipertensi sebanyak 31 orang yang dikumpulkan dengan concesutive sampling. Heipertensi diperoleh dengan pemeriksaan tekanan darah dan wawancara riwayat konsumsi obat anti hipertensi. Hasil penelitian didapatkan sampel berjumlah 31 orang yaitu 15 orang laki-laki dan 16 orang perempuan, dan kemudian sampel tersebut diberikan terapi musik klasik. Dengan hasil yaitu sebanyak 16 sampel mengalami penurunan tekanan darah dan 15 sampel tidak mengalami penurunan tekanan darah. Berdasarkan hasil analisis t-test dan Chi-Square didapatkan pengaruh musik klasik terhadap penurunan tekanan darah pasien penderita hipertensi (p value= 0,000). Maka penurunan tekanan darah pada pasien penderita hipertensi.